Effect of elastic-cord towing on the kinematics of the acceleration phase of sprinting - Corn, R. J.; Knudson, D. (The Journal of Strength and Conditioning Research, 2003)
We studied the specificity of elastic-cord towing by measuring selected kinematics of the acceleration phase of sprinting. Nine collegiate sprinters ran two 20-m maximal sprints (MSs) and towed sprints (TSs) that were recorded on high-speed video (180 Hz). Sagittal plane kinematics of a 4-segment model of the right side of the body were digitized for a complete stride at the 15-m point for the fastest trial. Significant (p < 0.001) differences were observed for horizontal velocity of the center of mass (CoM), stride length (SL), and horizontal distance from the CoM of the foot to the CoM of the body. There was no significant difference in stride rate between the MS and TS conditions. Omega-squared analysis showed that elastic-cord towing accounted for most of the variance in acute changes in horizontal velocity (73%), SL (68%), and horizontal position of the CoM at foot contact (64%). Elastic-cord tow training resulted in significant acute changes in sprint kinematics in the acceleration phase of an MS that do not appear to be sprint specific. More research is needed on the specificity of TS training and long-term effects on sprinting performance.